Volatilization of ammonia in pasture fertilized with nitrogen sources - Menezes das Chagas, Paulo Henrique; Cabral Gouveia, Geraldo Candido [UNESP]; Silva da Costa, Geany Giovana; Sousa Barbosa, Willams Ferreira; Alves, Ana Carolina (Univ Estadual Mato Grosso Sul, 2017)
Nitrogen fertilization is essential for increasing tropical forage production, however, the nitrogen (N) source and factors as management used can cause high ammonia (NH3) losses for volatilization. The present work was conducted with objective to quantify N losses by NH3 volatilization of nitrogen sources in pasture area. The experiment was developed at the State University of Mato Grosso do Sul (UEMS), in Cassilandia, MS, Brazil using the experimental design in randomized blocks with four treatments (urea; urea coated with polymer; urea treated with NBPT; and, ammonium nitrate) and five repetitions. Being applied at dosage equivalent to 100 kg ha(-1) of N. For quantification of volatilization NH3 were used absorbing foams, placed 1.0 cm from the soil surface. Losses of NH3 volatilization were lower when urea treated with NBPT (N-(n-butil) tiofosforico triamida) and urea coated with polymer when compared to the use of conventional urea. The urea treated with NBPT delayed the peak volatilization in two days in relation to other sources.
Keywords: forage; Urochloa; NH3; urea